Dental caries in the primary dentition in public nursery school children in Juiz de Fora, Minas Gerais, Brazil - Leite Isabel Cristina Gonçalves; Ribeiro Rosangela Almeida (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2000)
The aim of this study was to assess the prevalence of dental caries in the primary dentition and associated variables in low socioeconomic preschool children enrolled in public nursery schools in Juiz de Fora, Minas Gerais, Brazil. Four public institutions were selected by geographic criteria (two in the central region and two in the peripheral region). The study population comprised 338 children (181 boys; 157 girls) aged 2-6 years old. Dental caries was recorded using the decayed, missing, and filled teeth (dmf-t) index. Among the examined children, 50.6% were caries-free. The mean dmf-t index was 2.03. It was higher in the peripheral nursery schools (p < 0.01). A trend towards a difference between sexes (p = 0.06) was observed. Logistic regression analysis selected a previous child's visit to dentist (p < 0.001), geographic location of the public nursery school (p < 0.01), and age (p < 0.01) as predictive variables for the dmf-t index. The study showed the need for an oral health program for this population, including both curative and preventive measures in order to achieve the WHO/FDI goals for the year 2000, namely 50% of children free of caries at age 5-6 years.